The PreAmplifier ShAper for the ALICE TPC detector - Soltveit, Hans Kristian; Stachel, Johanna (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2012)
In this paper the PreAmplifier ShAper (PASA) for the Time Projection Chamber (TPC) of the ALICE experiment at LHC is presented. The ALICE TPC PASA is an ASIC that integrates 16 identical channels, each consisting of Charge Sensitive Amplifiers (CSA) followed by a Pole-Zero network, self-adaptive bias network, two second-order bridged-T filters, two non-inverting level shifters and a start-up circuit. The circuit is optimized for a detector capacitance of 18-25pF. For an input capacitance of 25pF, the PASA features a conversion gain of 12.74mV/fC, a peaking time of 160ns, a FWHM of 190ns, a power consumption of 11.65mW/ch and an equivalent noise charge of 244e+17e/pF. The circuit recovers smoothly to the baseline in about 600ns. An integral non-linearity of 0.19% with an output swing of about 2.1V is also achieved. The total area of the chip is 18mm2 and is implemented in AMS's C35B3C1 0.35μm CMOS technology. Detailed characterization tests were performed on about 48000 PASA circuits before mounting them on the ALICE TPC front-end cards. After more than two years of operation of the ALICE TPC with p-p and Pb-Pb collisions, the PASA has demonstrated to fulfill all requirements.